Developing Energy Conversion Teaching Material Based on Discovery Learning Model Through Scientific Approach - Supriadi, Supriadi; Suparno, Suparno; Maksum, Hasan; Lapisa, Remon (Universitas Pendidikan Ganesha, 2020)
Energy conversion material is material that requires a more detailed and broad understanding and explanation of the material. To be able to improve students' understanding, a discovery learning model teaching material is needed through a scientific approach oriented to problems related to real life. The purpose of this study is to produce teaching materials that are valid, practical and effective in the field. This type of research is research and developmentÂ with a 4-D (four-D) development model. The subjects of this study were students of class X Automotive Light Vehicle Engineering Vocational High School 1 Padang. The instruments used were validation sheets, teacher and student response questionnaires, and learning achievement tests.The results obtained from this development research are as follows: (1) Generating teaching materials for discovery learning models through a scientific approach. (2) The results of the analysis of the validity of teaching materials to experts obtained an average of 0.910> 0.667 with a valid category, (3) The results of the practicality analysis of teaching materials from the teacher's response were 87.33% with a very practical category and students' responses were 91.26% with a very practical category (4) The results of the analysis of the effectiveness of teaching materials are assessed from the results of the pretest and posttest, the gained score is 0.59 in the medium category. The study provides evidence that discovery learning model teaching material through scientific approach is valid, practical and effective to use.